Tingkat Kepuasan Peserta GMC-Askes Terhadap Mutu Pelayanan Kesehatan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Health Insurance based Gadjah Mada Medical Centre (GMC), was established to overcome students' health problems and rising health service cost. The developing knowledge and technology leads to improve health service and professionalism. Therefore, in accordance to the GMC vision, service quality must be prioritised. Measuring member satisfaction level is one way to improve quality service. This study was aimed to find out the satisfaction level of members to GMC services and associated factors with satisfaction level, and to obtain representation about members' expectation of GMC service. This was quantitative and qualitative methods with a cross sectional study. The systematic random sampling technique with 250 respondents was used to obtain sample from first line (gate keeper) service. The measurement was taken from disconfirmation-scale, closed questionnaires and opened questions. While research for the referal level of outpatient (RJTL) and the in-patient (Ranap) services were performed through focused group discussion (FGD). The result of the study in gate keeper level showed that 4,4% respondents are not satisfied, 82.0% are satisfied enough, and 13.2% are satisfied, and 0,4% are very satisfied. Experience become member of the other Health Insurance is significantly associated with satisfaction level (p < 0.05). Responsiveness dimension is most dominant to satisfaction level. Respondents expectation are mostly about waiting room comfort, waiting time, quality and supply of drug, accurate, information and empathy of doctor. Expectation for RJTL and Ranap were about the improvement in financial administration, medical services, and paramedics. It was concluded that the members were satisfied with the service but still have a high expectation for improvement. The satisfaction level is significantly associated with experience become member of the other Health Insurance.